Increased expression of TRPM8 and p21/Cip1 in epithelial carcinoma cells in confluent conditions - Fujino, Tomofumi (Fundamental Toxicological Sciences, 2025)
Based on that TRPM8 is a key factor of normal cell-carcinoma cell interaction and there is a tendency for proliferation of some cell types that are repressed in a high-density state rather than in a low-density state, we attempted to clarify the relationship between direct cell-cell interactions and expression of TRPM8, repressor of carcinoma cell proliferation. We examined TRPM8 and p21/Cip1 levels in normal and carcinoma epithelial cells at low and high cell density (confluent). TRPM8 and p21/Cip1 levels in confluent carcinoma cells markedly increased as compared with that of carcinoma cells in low density and normal cells in low density and confluent. When carcinoma cells cultured to confluent were re-seeded at low density, TRPM8 and p21/Cip1 levels decreased, indicating that the direct cell-cell interaction may regulate the expression of TRPM8 and p21/Cip1 in carcinoma cells. Totally, TRPM8 functions as repressor of cell proliferation in the condition which enables direct interaction between carcinoma cells occurs.